New soft X‐ray beamline BL07LSU at SPring‐8. (11th February 2014) - Yamamoto, Susumu; Senba, Yasunori; Tanaka, Takashi; Ohashi, Haruhiko; Hirono, Toko; Kimura, Hiroaki; Fujisawa, Masami; Miyawaki, Jun; Harasawa, Ayumi; Seike, Takamitsu; Takahashi, Sunao; Nariyama, Nobuteru; et al.
<x xml:space="preserve">Abstract</x> A new soft X‐ray beamline, BL07LSU, has been constructed at SPring‐8 to perform advanced soft X‐ray spectroscopy for materials science. The beamline is designed to achieve high energy resolution (E/ΔE> 10000) and high photon flux [>1012 photons s−1 (0.01% bandwidth)−1] in the photon energy range 250–2000 eV with controllable polarization. To realise this state‐of‐the‐art performance, a novel segmented cross undulator was developed and adopted as a light source. The details of the undulator light source and beamline monochromator design are described. The achieved performance of the beamline, such as the photon flux, energy resolution and the state of polarization, is reported.